A GENDER-PERSPECTIVE EMPOWERMENT AND STRENGTHENING MODEL IN TTU DISTRICT BY YABIKU - ADEODATA LANIRIA CHARLA BARROS MBIRI; M. Angela Merici Siba; Fridus Bria (JURNAL ILMU SOSIAL DAN ILMU POLITIK, 2026)
This study examines the "Gender Perspective Empowerment and Strengthening Model in TTU Regency by Yabiku". The author's reason for studying this is because it is seen from the phenomenon of violence against women in TTU Regency which is quite high and the phenomenon of violence against women is categorized as a global problem. In theory, based on previous research searches, no one has studied the problem of violence against women which is studied through the "Gender Perspective Empowerment and Strengthening Model in TTU Regency by Yabiku". The urgency of this study expands the study of violence against women, and the results of this study can be used as a reference for consideration in decision-making and programs for preventing and handling violence against women. This study uses the "ACTORS" empowerment theory put forward by Sarah Cook and Steve Macaulay as a knife in examining the focus of the study, and uses a qualitative research method with a purposive method of selecting informants, namely members of the Yabiku NGO, empowerment participants, and several informants related to this study. The selection of these informants was chosen deliberately with the consideration that these informants are more knowledgeable about the focus of the research being studied. The data analysis technique used was Sugiyono's method: collecting, presenting, reducing, and drawing conclusions. The study found that the Yabiku NGO implemented three gender-based empowerment models: 1) Victim Assistance, 2) Economic Empowerment, 3) Political Empowerment. These three empowerment models have their own unique approaches and are capable of addressing cases of violence against women in TTU Regency. However, several obstacles remain in their implementation due to the dynamic nature of the community.